EFFORTS TO IMPROVE PERSONAL HYGIENE HABITS IN HAND WASHING BY MEANS OF DEMONSTRATION METHODS IN 5-6 YEAR OLD (Qualitative Studies In The Kebontalo Selong of 2020) - Diah Larasati Rahil; Fahruddin Fahruddin; Ika Rachmayani (Indonesian Journal of Elementary and Childhood Education, 2020)
The study is aimed at seeing how efforts to improve the personal hygiene habits of hand washing activities in the 5-6 year old children in the Kebontalo Selong environment. The type of research used was descriptive qualitative research. Subject of study of 6 child. The method of data collection used is observation, interview, and documentation. The data analysis used is qualitative descriptive analysis. Studies have shown that efforts to improve personal hygiene habits in hand washing by means of demonstration methods in the 5-6 year old in Kebontalo Selong environment of 2020. At the first stage of research, the child’s average score is at 25% to 33,3%, at the second stage the child’s average score is at 41,7% to 54,2%, at the third stage the child’s average score 62,5% to 70,8%, and at the fourth stage the child’s average score at 70,8% to 87,5%. This suggests the personal hygiene behaviors of children in hand washing activities are improved by the expected value of each child’s final status. The result of this study could be concluded that the use of emonstration methods would improve personal hygiene habits of hand washing activities in the 5-6 year old children in the Kebontalo Selong environment.